Amphiphilic beads as depots for sustained drug release integrated into fibrillar scaffolds - Gaharwar, Akhilesh K. (2014)
Native extracellular matrix (ECM) is a complex fibrous structure loaded with bioactive cues that affects the surrounding cells. A promising strategy to mimicking native tissue architecture for tissue engineering applications is to engineer fibrous scaffolds using electrospinning. By loading appropriate bioactive cues within these fibrous scaffolds, various cellular functions such as cell adhesion, proliferation and differentiation can be regulated. Here, we report on the encapsulation and sustained release of a model hydrophobic drug (dexamethasone (Dex)) within beaded fibrillar scaffold of poly(ethylene oxide terephthalate)-poly(butylene terephthalate) (PEOT/PBT), a polyether-ester multiblock copolymer to direct differentiation of human mesenchymal stem cells (hMSCs). The amphiphilic beads act as depots for sustained drug release that is integrated into the fibrillar scaffolds. The entrapment of Dex within the beaded structure results in sustained release of the drug over the period of 28days. This is mainly attributed to the diffusion driven release of Dex from the amphiphilic electrospun scaffolds. In vitro results indicate that hMSCs cultured on Dex containing beaded fibrillar scaffolds exhibit an increase in osteogenic differentiation potential, as evidenced by increased alkaline phosphatase (ALP) activity, compared to the direct infusion of Dex in the culture medium. The formation of a mineralized matrix is also significantly enhanced due to the controlled Dex release from the fibrous scaffolds. This approach can be used to engineer scaffolds with appropriate chemical cues to direct tissue regeneration